Pemberdayaan Kelompok Tani Pade Girang Melalui Sosialisasi dan Pelatihan Pembuatan Bolu Pisang - Setiawan, Rifani Nur Sindy; Anna Apriana Hidayanti; Baiq Rika Ayu Febrilia; I Ketut Budastra; Anas Zaini (Universitas Mataram, 2025)
The Pade Girang Farmers Group is one of the farmer groups in Landah Village, Praya Timur District, Central Lombok Regency. The types of farming they are engaged in are tobacco and paddy. In addition to these two commodities, Landah Village also has abundant natural resources and the harvest period is not dependent on the season, namely bananas. However, partners do not have the skills to process the existing local potential, namely bananas. So this activity aims to provide skills in the form of training in processing banana fruit innovation into banana cake in order to increase the economic value of existing resources. From the results of the community service, it was concluded that: (1) The response of the female members of the Pade Girang farmer group to the material that had been provided showed positive things; (2) Partners were able to produce banana cake independently so that it could have economic value and could increase the income of farming families apart from the agricultural sector; (3) There was a significant increase in the level of knowledge and skills of the female members of the Pade Girang farmer group regarding processed banana fruit products.